2003
DOI: 10.1080/0954012031000068335
|View full text |Cite
|
Sign up to set email alerts
|

Surviving the sex trade: A comparison of HIV risk behaviours among street-involved women in two Canadian cities who inject drugs

Abstract: In Canada, very little is known about the factors and processes that cause drug-related harm among female intravenous drug users (IDUs). Women who inject drugs and participate in the survival sex trade are considered to be at increased risk for sexual and drug-related harms, including HIV infection. Between September 1999 and September 2000, women participating in the VIDUS cohort in Vancouver and the St. Luc Cohort in Montreal completed interviewer-administered questionnaires. Analyses were conducted to compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 25 publications
4
76
1
2
Order By: Relevance
“…2,19,21,24,27 The majority of sex workers in this study had fi rst used crack before they fi rst sold sex, suggesting that crack addiction may force some into turning to sex work to support their addiction. The early initiation (around 8-11 years old) of any drug use among participants may also facilitate addiction, which in turn may increase the likelihood of entry into prostitution as a means of supporting their drug dependence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,19,21,24,27 The majority of sex workers in this study had fi rst used crack before they fi rst sold sex, suggesting that crack addiction may force some into turning to sex work to support their addiction. The early initiation (around 8-11 years old) of any drug use among participants may also facilitate addiction, which in turn may increase the likelihood of entry into prostitution as a means of supporting their drug dependence.…”
Section: Discussionmentioning
confidence: 99%
“…These behaviors place females who use crack cocaine at high risk for HIV/ AIDS, other STIs, tuberculosis, and viral hepatitis. 21 Female crack cocaine users interviewed in our study face a crucial problem: the scarcity, or even inexistence, of health services available to this population. This lack of access to health services is infl uenced by different factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19] Overall, few individuals reported recent unprotected sex with more than one person, confirming the data of a study among female injection drug users from Vancouver and Toronto. 20 Summarising all vulnerability factors, our data indicate that a significant proportion of individuals and more women than men reported multiple experiences that compromise their sexual health exponentially.…”
Section: Resultsmentioning
confidence: 99%
“…For example, IDUs injecting cocaine display higher frequencies of injecting than non-cocaine injectors, often occurring in the form of high-risk injection »binges« (Bourgois et al, 2000). In the VIDUS cohort, cocaine injection has been identified as a predictor of both HIV and HCV prevalence (Patrick et al, 1997;Spittal et al, 2003). Reviews of overdose mortality among IDUs have identified (combination) drug use -specifically involving opioids and cocaine -as a major determinant of overdose fatality (O'Driscoll et al, 2001;Coffin et al, 2003;Darke & Hall, 2003).…”
Section: Risks and Harms Associated With Cocaine And Crack Usementioning
confidence: 99%